Respostas
respondido por:
1
A) x^2 - x - 12 = 0 Delta: Δ = b^2 - 4ac Δ = (- 1)^2 - 4.1.(-12) Δ = 1 + 48 Δ = 49 Bhaskara: x' = - b ± √ Δ / 2a x' = - (-1) ± √49 / 2.1 x' = 1 + 7/2 x' = 8/2 x' = 4 x" = 1 - 7/2 x" = - 6/2 x" = - 3 B) 3x^2 - 9x + 5 = 0 Delta: Δ = b^2 - 4ac Δ = -(-9)^2 - 4.3.5 Δ = 81 + 60 Δ = 141 Bhaskara: x = - b ± √Δ / 2a x' = -(-9) + √141 / 2.3 x' = 9 + 11,9/6 x' = 20,9/6 x' = 3,5 x" = 9 - 11,9/6 x" = - 2,7/6 Aproximamos: - 2,7 para 3 ,assim, x" = -3/6 x" = - 1/2 C) 4x^2 - 10x - 4 = 0 Delta:
Δ = b^2 -4ac Δ = (-10)^2 - 4.4.(-4) Δ = 100 - 64 Δ = 36 Bhaskara: x = - b ± √ Δ / 2a x' = - (-10) ± √36 / 2.4 x' = 10 + 6/8 x' = 16/8 x' = 2 x" = 10 - 6/8 x" = 4/8 x" = 1/2
Δ = b^2 -4ac Δ = (-10)^2 - 4.4.(-4) Δ = 100 - 64 Δ = 36 Bhaskara: x = - b ± √ Δ / 2a x' = - (-10) ± √36 / 2.4 x' = 10 + 6/8 x' = 16/8 x' = 2 x" = 10 - 6/8 x" = 4/8 x" = 1/2
respondido por:
0
Resposta:
A) x^2 - x - 12 = 0 Delta: Δ = b^2 - 4ac Δ = (- 1)^2 - 4.1.(-12) Δ = 1 + 48 Δ = 49 Bhaskara: x' = - b ± √ Δ / 2a x' = - (-1) ± √49 / 2.1 x' = 1 + 7/2 x' = 8/2 x' = 4 x" = 1 - 7/2 x" = - 6/2 x" = - 3 B) 3x^2 - 9x + 5 = 0 Delta: Δ = b^2 - 4ac Δ = -(-9)^2 - 4.3.5 Δ = 81 + 60 Δ = 141 Bhaskara: x = - b ± √Δ / 2a x' = -(-9) + √141 / 2.3 x' = 9 + 11,9/6 x' = 20,9/6 x' = 3,5 x" = 9 - 11,9/6 x" = - 2,7/6 Aproximamos: - 2,7 para 3 ,assim, x" = -3/6 x" = - 1/2 C) 4x^2 - 10x - 4 = 0 Delta:
Δ = b^2 -4ac Δ = (-10)^2 - 4.4.(-4) Δ = 100 - 64 Δ = 36 Bhaskara: x = - b ± √ Δ / 2a x' = - (-10) ± √36 / 2.4 x' = 10 + 6/8 x' = 16/8 x' = 2 x" = 10 - 6/8 x" = 4/8 x" = 1/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás